Penyelesaian Perselisihan Hubungan Industrial Berdasarkan Undang-Undang Penyelesaian Perselisihan Hubungan Industrial: Studi Kasus : PT. Orson Indonesia - Rafi Muhammad Irvan; Raffi Ikzaaz Abdallah; Raihan Ramadhan Hayatuddin (IAI Nasional Laa Roiba Bogor, 2024)
Termination of Employment (PHK) is a highly burdensome action for workers, necessitating robust legal protection. This protection includes prevention efforts, PHK prohibitions, valid reasons for PHK, and compensation rights that workers should receive, such as severance pay, long service pay, compensation for entitlements, and separation pay. Legal protection for workers in PHK cases is divided into three main categories: PHK procedures, PHK reasons, and PHK compensation rights that must be fulfilled by employers. If employers do not adhere to the procedures and reasons stipulated by law, the PHK is considered invalid, and workers must be reinstated. This study employs a normative legal research method, examining literature or secondary data to uncover relevant legal rules, principles, and doctrines. Secondary legal materials used include labor-related regulations, literature in the field of industrial relations, and court decisions.